Literature Review: The Use of Augmented Reality Learning Media Oriented Towards Science Process Skills to Enhance Student Understanding and Scientific Attitudes Towards Genetics - Baharuddin, Rahmat; Surtikanti, Hertien Koosbandiah; Riandi, Riandi (Universitas Negeri Makassar, 2023)
Abstract. Integrating technology in education may vary in many forms. Augmented reality is an technology-oriented learning media that integrating real and virtual world to enhance the realness of an object. Genetics topic has main area in cellular and molecular object, so it is hard to learn because student can not directly observe the topics’ object. Learning genetics need an indepth and comprehensive analysis. Learning method that integrating various scientific skills can guide student to learn by analyzing the concept. Scientific Process Skills (SPSs) method make learning become meaningful. This research is using literature review method to study the potential of using augmented reality as learning media to teach genetics topic. The results show that augmented reality as a learning media has a big potential to improve genetics topic teaching and learning while integrating SPSs based learning to improve students’ knowledge and scientific attitudes to make the learning process as a whole.Keywords: augmented reality, genetics, science process skills, scientific attitudes.